A trajetória da participação popular no planejamento urbano : o caso do Conselho Municipal do Plano Diretor de Vitória (1984-2001) - Marchezini, Flávia de Sousa (2006)
The subject of the participationes experiences in the public administration here is dealt with from the analysis to the one the relations between State and Society, in the theoretical field, as well as of the trajectory of the democratic institutions and the social movements in Brazil and local scope, with approach in the process of urbanization and the social demands for it generated. For such historical analysis the experience of the advice is overcome as referring empiricist Municipal theatre of the Urban Managing Plan, created in 1984, and of initiative of Municipal government of the City of Victory, capital of the Espirito Santo. Search to evaluate the relations of being able that they are established in the interior of this public space, by means of the examination of acts, resolutions and proposals of the advice, local periodicals of the time and interviews of the council members, during the studied period (1984 the 2001). Using of approach present theoretician in the workmanships of Michel Foucault and Jürgen Habermas among others and of the circumstancial evidence paradigm of inquiry of Carlo Ginzburg, evidenced that the influential people of participation of the civil society in the advice, associate to the speech tecno-bureaucratic it leads to the fragility of the participation of the representatives of the truily popular sectors, ahead of the mechanisms of being able existing in the interior of this said cell participationes.